Pengembangan Perangkat Pembelajaran IPA Berorientasi pada Taxonomy for Science Education di Sekolah Dasar - Awang, Imanuel Sairo; Andri, Andri (Mimbar Sekolah Dasar, 2017)
The learning method has been focused on student cognitive. In the mean time, student should accept comprehensively. This research is aim to develop learning kits of natural science that taxonomy for science education oriented in elementary school. The kits consist of domain I (imagine and understanding), domain II (science process skills), domain III (imagine and creativity), domain IV (attitude and value), and domain V (conection and applying). This is a research and development method, with subjects were both of fourth grade elementary school students of SD negeri 20 Mambok and SD Negeri 5 Sintang. The results of evaluation of learning science experts to examine the validity of the learning kits stated valid. Then, the trial results showed that the learning kits was developed to meet the criteria of effective to use in elementary school. It concludes that the learning kits of natural science that taxonomy for science education oriented is able to applied in elementary school.